Life, but not as we know it: A.I. and the popular imagination - Goode, Luke (Culture Unbound, 2018)
Advances in artificial intelligence (A.I.) are prompting a growing chorus of both excitement and anxiety. A.I. is widely perceived as a significant emerging and future-shaping technological field that is developing at an accelerating rate. As such, futuristic imagery involving A.I. is increasingly prevalent in popular media. A central task for critical future studies is to assess both positive and problematic aspects of the futuristic scenarios offered up for public consumption, and to evaluate their role as part of a ‘futural public sphere’ (Goode & Godhe 2017). In this paper, I discuss three distinct but interwoven strands of public discourse that each have a role to play in shaping the popular imagination around possible A.I. futures. I begin with a selective discussion of mainstream science fiction represenations. Secondly, I consider several recent and high-profile popular media events surrounding real-world developments in A.I. Finally, I turn to contemporary futurology and, specifically, the discourse of the ‘singularity’ which posits a near future in which artificial ‘superintelligence’ outstrips human cognitive capacities. In this paper I argue that, while much popular coverage of A.I. is sensationalist and potentially misleading, public engagement with a complex, technical subject such as this depends on the circulation of ’evocative stories’ which can act as entry points into public debate. As such, it is important to understand the evocative power of the stories we frequently tell ourselves in popular discourse about A.I. and its role in our future.